UPAYA PEMERINTAH TURKI UNTUK BERGABUNG DENGAN UNI EROPA - Adhi Wardana (Universitas Komputer Indonesia, 2017)
The European Union is an inter-governmental organization whose members are European countries. Since July 1, 2013 already has 28 member countries, many countries of the European region who want to join the European Union, one of which is Turkish, the extent to which the Turkish government's efforts to join the European Union? This study aims to determine the extent of the Turkish Government Efforts To Join The European Union (2004-2008). To be able to Turkey joining the European Union must meet the Copenhagen criteria which consists of the political criteria, economic and acquis, Turkey must conform to all the regulations of the European Union so researchers try to analyze from the effort, constraints, and prospects for Turkey to join the European Union. This type of research is a qualitative research method used is descriptive analysis techniques. aims to describe the facts related to the problem under study. Most of the data that is collected through library research, online data retrieval, and documentation, data were then analyzed with a theoretical approach to dealing with International Relations. The results showed that the Turkish government has made progress in meeting the criteria candidates are awarded by the European Union, Turkey showed promising economic growth, recorded during the year 2004-2008 Turkish economic growth averaged 7%. Turkey managed to adopt new chapters in the Acquis criteria, although there are many other chapters that have not adapted to the European Union, in the political aspects of the Turkish government has been working hard to solve the problem of ham with the Kurds, Armenia and Cyprus, but in line with the efforts that have been The Turkish government in its application, there are still many obstacles that eventually make Turkey's accession to EU membership back hampered..